Virulence factors and genetic variability of vaginal Candida albicans isolates from HIV-infected women in the post-highly active antiretroviral era - Zanni, Pâmela Cristina Mastellaro Delvas (2017)
Vulvovaginal candidiasis (VVC) in HIV-infected (HIV+) women is a serious public health problem. However, little is known about the virulence mechanisms of vaginal Candida albicans from HIV+ women in the post-highly active antiretroviral therapy (HAART) era. Here, we report a comparative analysis of the expression of key virulence factors and genetic variability of 26 vaginal C. albicans strains isolated from HIV+ women undergoing HAART and 18 from HIV-uninfected (HIV-) women. In general, we observed that C. albicans from HIV+ women receiving HAART showed lower expression of virulence factors compared with C. albicans from HIV- women, except for the proteinase activity which is highly expressed. The results in HIV-women further suggest that virulence factors appear to be expressed in response to the yeast stress, in the presence of an adequate immune response. Furthermore, the RAPD results showed a high heterogeneity among isolates from both groups of women. These findings in HIV+ women using HAART will help to improve the monitoring of vaginal yeast infections and the quality of life of patients.